RPM Sensor-Based Revitalization of Multipurpose Chopping Machine in Margourip: Revitalisasi Mesin Pencacah Serbaguna Berbasis Sensor RPM di Margourip - Mulyadi, Akhmad; Syahrorini, Syamsudduha; Anggraeni, Putri Ayunda; Farhan, Muhammad; Ananda, Mohammad Azrul (Proceedings of The ICECRS, 2025)
General Background: Technological innovation in agricultural machinery plays a critical role in enhancing waste processing efficiency and supporting sustainable farming practices. Specific Background: In Margourip Village, a multipurpose chopping machine used to process pineapple stump waste into animal feed was underperforming due to blunt blades, a suboptimal drive system, and the lack of a speed measurement mechanism. Knowledge Gap: There is limited application of precision-enhancing technology, such as RPM sensors, in revitalizing existing agricultural equipment at the village level. Aims: This community service project aims to revitalize the chopping machine by improving its mechanical components and integrating RPM sensor technology to increase the accuracy and consistency of its operation. Results: Using a Research and Development (R&D) approach, the program involved field surveys, 3D Blender-based design simulations, machine repair, and testing. Key improvements included blade sharpening, optimization of the drive system, and RPM sensor installation. These interventions resulted in increased shredding efficiency, more uniform output, and extended machine durability. Novelty: The integration of 3D modeling and RPM sensor technology in a community-level agricultural machine represents a novel approach to minimizing implementation errors and improving operational precision. Implications: The revitalized machine enhances local agricultural waste processing, supports the sustainability of small-scale farming, and can serve as a replicable model for technological upgrades in rural settings. The program's outcomes also open pathways for future development, including the use of advanced materials and automation to further improve performance. Keywords: Chopping Machine, RPM Sensor, Agricultural Waste, 3D Modeling, Margourip Village Highlights: Machine revitalization includes blade sharpening and system redesign. RPM sensor integration improves speed accuracy and output uniformity. 3D Blender modeling minimizes technical errors before implementation.